2010
DOI: 10.1007/s00134-010-2040-0
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin receptor antagonist attenuates inflammatory response and prolongs the survival time in a neonatal sepsis model

Abstract: ETR-P1/fl treatment significantly attenuated the elevation of NOx, TNF-α, and HMGB-1, which improved the systemic hypotension, pulmonary hypertension, and blood gases, thereby causing improvement of survival time in a progressive neonatal sepsis CLP model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
2
16
1
2
Order By: Relevance
“…In our sepsis model, we observed an elevation in nitric oxide metabolites levels in the CLP group (19). We have previously reported that ETR-P1/fl inhibits the elevation of nitric oxide metabolites, which may help to maintain mean arterial pressure in the ETR-P1/fl group as compared with that in the CLP group (16). A previous study has similarly indicated that ETR-P1/fl treatment suppresses NO synthesis (35).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In our sepsis model, we observed an elevation in nitric oxide metabolites levels in the CLP group (19). We have previously reported that ETR-P1/fl inhibits the elevation of nitric oxide metabolites, which may help to maintain mean arterial pressure in the ETR-P1/fl group as compared with that in the CLP group (16). A previous study has similarly indicated that ETR-P1/fl treatment suppresses NO synthesis (35).…”
Section: Discussionsupporting
confidence: 54%
“…It also attenuates inflammatory responses during sepsis (15). We have previously suggested that ETR-P1/fl could have a suppressive effect on the release of inflammatory cytokines, including tumor necrosis factor-α and the highly mobile group-1 box protein, and could prolong survival time (16).…”
mentioning
confidence: 99%
“…These animals develop rapid hemodynamic changes and microvascular dysfunction that are not the same as in adult rats (Seely et al, 2011;Sims et al, 2014). Neonatal, 3-day-old piglets subjected to CLP show deterioration of cardiac output, pulmonary hypertension, and shock (Goto et al, 2010), consistent with cold shock (low cardiac output with high systemic vascular resistance) frequently observed in newborns and infants with severe sepsis (Wheeler et al, 2011).…”
Section: Animal Modelsmentioning
confidence: 99%
“…18 Of note, several of these cytokines (e.g., IL-1β, iNOS) have also been implicated in endotoxin-induced PA dysfunction, 6 and in this context, inhibition of ET-1 signaling has been demonstrated to improve outcomes in experimental sepsis. 19 ET-1 acts via two receptors that are highly expressed in the pulmonary vasculature: endothelin receptor A (ET A R) and endothelin receptor B (ET B R). Both ET A R and ET B R are expressed on PA smooth muscle cells (PASMCs), where they mediate PA vasoconstriction.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, two previous studies demonstrated beneficial effects of selective ET A R inhibitors during endotoxemia. 19,25 However, mechanistic studies investigating the effects of ET A R inhibition on pulmonary vascular tone and proinflammatory markers in the pulmonary vasculature have not yet been performed. We set out to investigate the effects of the selective ET A R antagonist sitaxsentan on hemodynamic and physiologic parameters in a rat model of endotoxemia.…”
Section: Introductionmentioning
confidence: 99%